Emergency Preparedness of The New Generation Retail Outlets of Kerala - Roshan, R.; Kinslin, D. (International Journal of Engineering and Technology, 2018)
The aim of this research study is to analyze the preparedness of the new generation retail outlets of Kerala to face an unexpected emergency situation. Kerala is a small south Indian state with 580km of its western boundary as a coastal line to the Arabian sea. With a population density of 860 people per square kilometer and a human development index of 0.79 which is the highest in the country, the state is multi hazard prone, though it ranks high in education health, and purchasing power. The last decade has seen a tremendous increase in the number of organized retail outlets in the state. With 14.5% of the state prone to floods, 14.4% of the area prone to landslides and with an average of 70 people dying of lightning every year this consumer state has to be more conscious about the safety measures existing in the new generation sales outlets. This study was focused on discovering the awareness, the presence, the maintenance and the usage of emergency management systems in the new generation retail outlets. The data was collected using interview schedule and observation. The result of the study shows an alarming nature of general negligence to even the simplest precautions that could be taken.Â